A figurational approach to environmental sustainability in the context of sport - Cain, Alison (Frontiers in Sports and Active Living, 2023)
Discourses around environmental sustainability and climate change are increasingly prominent in the sports sector, with a growing range of sports organisations developing policies to address these issues. This paper contends that figurational (or process) sociology can offer a useful framework for examining the development of policy as a process in the context of sport and, specifically, mega-events. The Olympic Games serve as an example for purposes of contextualisation, illustrating four interconnected dimensions of figurational sociology: lengthening chains of interdependence, established-outsider power relations, internalisation of social values, and unintended consequences. Further, the paper seeks to highlight the utility of a figurational perspective particularly when this is enhanced through the integration of complementary concepts, namely knowledge transfer, isomorphism, and diffusion of innovations. Thus, it is asserted that a blended figurational approach can help facilitate understanding of interdependencies and dynamic power relations across expanded stakeholder networks in relation to sports mega-events. Finally, the paper touches on the relevance of sport in relation to the United Nations (UN) Sustainable Development Goals to highlight the need for policy coherence that is arguably unachievable without the understanding of stakeholder interdependencies and power relationships a figurational lens enables. Such understanding is therefore considered to be important as a foundation for the enactment of meaningful policy in the fight against climate change.